Harmonizing community-based health worker programs for HIV: a narrative review and analytic framework - De Neve, Jan-Walter; Boudreaux, Chantelle; Gill, Roopan; Geldsetzer, Pascal; Vaikath, Maria; Bärnighausen, Till; Bossert, Thomas John (Human resources for health, 2017)
Background: Many countries have created community-based health worker (CHW) programs for HIV. In most of these countries, several national and non-governmental initiatives have been implemented raising questions of how well these different approaches address the health problems and use health resources in a compatible way. While these questions have led to a general policy initiative to promote harmonization across programs, there is a need for countries to develop a more coherent and organized approach to CHW programs and to generate evidence about the most efficient and effective strategies to ensure their optimal, sustained performance.Methods: We conducted a narrative review of the existing published and gray literature on the harmonization of CHW programs. We searched for and noted evidence on definitions, models, and/or frameworks of harmonization; theoretical arguments or hypotheses about the effects of CHW program fragmentation; and empirical evidence. Based on this evidence, we defined harmonization, introduced three priority areas for harmonization, and identified a conceptual framework for analyzing harmonization of CHW programs that can be used to support their expanding role in HIV service delivery. We identified and described the major issues and relationships surrounding the harmonization of CHW programs, including key characteristics, facilitators, and barriers for each of the priority areas of harmonization, and used our analytic framework to map overarching findings. We apply this approach of CHW programs supporting HIV services across four countries in Southern Africa in a separate article.Results: There is a large number and immense diversity of CHW programs for HIV. This includes integration of HIV components into countries’ existing national programs along with the development of multiple, stand-alone CHW programs. We defined (i) coordination among stakeholders, (ii) integration into the broader health system, and (iii) assurance of a CHW program’s sustainability to be priority areas of harmonization. While harmonization is likely a complex political process, with in many cases incremental steps toward improvement, a wide range of facilitators are available to decision-makers. These can be categorized using an analytic framework assessing the (i) health issue, (ii) intervention itself, (iii) stakeholders, (iv) health system, and (v) broad context.Conclusions: There is a need to address fragmentation of CHW programs to advance and sustain CHW roles and responsibilities for HIV. This study provides a narrative review and analytic framework to understand the process by which harmonization of CHW programs might be achieved and to test the assumption that harmonization is needed to improve CHW performance.